Housing provision in Malaysia: Changing role of state and market in the post asian financial crisis - Shuid, Syafiee (2008)
The debates on the role of state and market in the political economy have increase particularly since the 1980s with the rise of neo liberal ideology. Since then, the idea of market economy spread around the world including in most developing countries as propagated by the World Bank and International Monetary Funds (IMF). Most countries began to embrace the market reform and considerable retreat of the state from the direct economic intervention. Yet, the reforms in the overall economy sectors still uneven and show mixed result. In some countries, housing sector still remained an important aspect in politic and economic development particularly in East Asia. Since there is still lack of debates on the role of state and market in East Asia, therefore this paper aims to discuss the relationship between political economy development and housing provision. Using Malaysia as the case study, the paper will discuss the political economy development in Malaysia and the changing role of state and market in housing provision particularly after the Asian Financial Crisis 1997-1998.